Method for producing physically processed starch, and physically processed starch

The method of gelatinizing and physically processing starch reduces its viscosity, making it soluble in water and suitable for use as a food binder, addressing the handling challenges of high-viscosity starch products.

JP2025071349APending Publication Date: 2025-05-02FUTAMURA CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025029753
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-16
Filing Date
2025-02-27
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing starch products are insoluble in water, have high viscosity, and are difficult to handle, especially when used as food thickeners or coating materials, due to their high concentration and low flowability.

Method used

A method for producing physically processed starch that involves gelatinizing raw starch and subjecting it to multiple stages of physical treatment to reduce viscosity, resulting in a product that is soluble in water and has moderate viscosity, suitable for use as a food binder.

Benefits of technology

The processed starch exhibits a minimum peak viscosity of 40% or more and a final viscosity of 60% or more, making it easier to handle and use in various applications without significant changes in properties during heating and cooling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025071349000001_ABST
    Figure 2025071349000001_ABST
Patent Text Reader

Abstract

To provide a processed starch which is soluble in water and has appropriate viscosity.SOLUTION: There is provided a processed starch that has a minimum peak viscosity of 40% or more relative to the maximum peak viscosity of the glue solution measured by the following measuring method, and a final viscosity of 60% or more. (1) The processed starch is adjusted to a 10 wt.% aqueous suspension. (2) Stirring the aqueous suspension with a Rapid Visco Analyzer at a rotation speed of 160 rpm, the aqueous suspension is maintained at 50°C for 1 minute. (3) Then, the aqueous suspension is heated from 50°C to 95°C in 3 minutes and 42 seconds and is maintained at 95°C for 5 minutes. (4) Then, the aqueous suspension is cooled from 95°C to 50°C in 3 minutes and 48 seconds and is maintained at 50°C for 5 minutes. (5) During operations (2) to (4), the maximum peak viscosity, minimum peak viscosity, and final viscosity of the aqueous suspension are measured.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing physically modified starch and physically modified starch, and more particularly to a physically modified starch that is soluble in water and has a suitable viscosity, and a method for producing the physically modified starch. [Background technology]

[0002] Starch is often used as a thickening agent added to foods and as a coating material for soft capsules. Because starch is insoluble in water, it is gelatinized by heating before use, but when the starch concentration is high, the gelatinization results in high viscosity and low fluidity, making it difficult to handle. On the other hand, if the starch concentration is reduced to ensure a practical viscosity, the water retention increases, so when used as a coating material, the drying efficiency is poor and the coating tends to become thin due to the reduced solid content.

[0003] In addition, when used in food applications, it is required that it is soluble and has a low viscosity when dissolved in water, and that it does not affect the texture. For example, polysaccharides such as starch are soluble in warm water but insoluble in water at room temperature, and are difficult to handle because of their high viscosity when dissolved. Pullulan, which is soluble in water and has a low viscosity when dissolved, is difficult to use because it does not have sufficient binding power and is expensive.

[0004] Starch is known as pregelatinized starch, which is made soluble in water by gelatinization (gelatinization), drying and powdering. Although spray dryers are considered to be highly efficient for drying and powdering, they are not suitable for powdering highly viscous solutions, so drum dryers, which can dry even high-viscosity solutions, are used to dry and powder pregelatinized starch. However, drum dryers are more likely to introduce foreign matter than spray dryers, and improving the quality tends to be more time-consuming.

[0005] Polysaccharides that can be spray-dried using a spray dryer can be reduced in viscosity and solubilized by ultrasonic treatment (see, for example, Patent Document 1). Polysaccharides such as starch are irradiated with ultrasonic waves to modify them to the point where they have practical solubility and viscosity. However, since the treatment is carried out near the ultrasonic treatment irradiation point, the efficiency tends to be poor. In addition, there are problems with the difficulty of controlling the treatment, such as homogenizing the treatment and the generation of a metallic odor if the treatment is too uneven.

[0006] Also, a method has been proposed for narrowing the molecular weight distribution of starch or starch derivatives by using high-pressure homogenization treatment (see, for example, Patent Document 2). When the molecular weight distribution becomes narrow, the ratio of high molecules that ensure viscosity and low molecules that ensure solubility becomes biased, which makes it difficult to achieve both viscosity and solubility. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 4288381 [Patent Document 2] Special Publication Hei 10-506425

[0008] The present invention has been made in consideration of the above-mentioned points, and provides a processed starch that is soluble in water and has a suitable viscosity. Summary of the Invention [Means for solving the problem]

[0009] That is, the first invention relates to a processed starch having a minimum peak viscosity of 40% or more relative to the maximum peak viscosity of a paste measured by the following measurement method, and a final viscosity of 60% or more.

[0010] <Measurement method> (1) Prepare a 10% by weight suspension of the modified starch in water. (2) The aqueous suspension is stirred at 160 rpm using a Rapid Visco Analyzer and maintained at 50° C. for 1 minute. (3) Next, the temperature is increased from 50°C to 95°C in 3 minutes and 42 seconds, and then held at 95°C for 5 minutes. (4) Next, cool from 95°C to 50°C in 3 minutes and 48 seconds, and hold at 50°C for 5 minutes. (5) Measure the maximum peak viscosity, minimum peak viscosity, and final viscosity during the operations (2) to (4).

[0011] A second invention relates to the processed starch according to claim 1, which has a molecular weight dispersity (weight average molecular weight / number average molecular weight) of 13,000 to 35,000 in the first invention.

[0012] The third invention relates to a method for producing a modified starch according to the first or second invention, wherein the modified starch is used as a food binder.

[0013] The fourth invention relates to a method for producing a modified starch according to the first or second invention, wherein the starch raw material is waxy corn starch.

[0014] The fifth invention relates to a method for producing a modified starch according to the third invention, in which the starch raw material is waxy corn starch. Effect of the Invention

[0015] The processed starch according to the first aspect of the present invention has a minimum peak viscosity of 40% or more of the maximum peak viscosity of the paste measured by the above-mentioned measuring method, and a final viscosity of 60% or more. Therefore, the change in properties during heating and cooling is small, the starch is easy to handle, and the starch can be used in a variety of applications.

[0016] According to the processed starch of the second invention, since the molecular weight dispersity (weight average molecular weight / number average molecular weight) in the first invention is 13,000 to 35,000, it can have appropriate viscosity while being soluble in water.

[0017] According to the processed starch of the third invention, since the processed starch in the first or second invention is a food binder, it can impart appropriate binding properties to food.

[0018] According to the processed starch of the fourth invention, since the starch raw material in the first or second invention is waxy corn starch, the processed starch can have stable properties.

[0019] According to the processed starch of the fifth invention, since the starch raw material in the third invention is waxy corn starch, the processed starch can have stable properties. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a schematic diagram of a process for producing physically modified starch according to one embodiment of the present invention. [Diagram 2] 1 is a graph showing the change in viscosity of the physically processed starch of Prototype 1 with change in temperature. [Diagram 3] 1 is a graph showing the change in viscosity of the physically processed starch of Prototype 2 with change in temperature. [Figure 4] 1 is a graph showing the change in viscosity of the physically processed starch of Prototype 3 with change in temperature. [Diagram 5] 1 is a graph showing the change in viscosity of the physically processed starch of Prototype 4 with change in temperature. [Figure 6] 1 is a graph showing the change in viscosity of the physically processed starch of Prototype Example 5 with change in temperature. [Figure 7] 1 is a graph showing the change in viscosity of the physically processed starch of Prototype 6 with change in temperature. [Figure 8] 1 is a graph showing the change in viscosity of the physically modified starch of Prototype Example 7 with change in temperature. [Figure 9] 1 is a graph showing the change in viscosity of the starch of Comparative Example 1 with change in temperature. [Figure 10] 1 is a graph showing an HPLC chart of the physically modified starch of Prototype Example 1. [Figure 11] 1 is a graph showing an HPLC chart of the physically modified starch of Prototype Example 2. [Figure 12] 1 is a graph showing an HPLC chart of the physically modified starch of Prototype Example 3. [Figure 13] 1 is a graph showing an HPLC chart of the physically modified starch of Prototype Example 4. [Figure 14] 1 is a graph showing an HPLC chart of the physically modified starch of Prototype Example 5. [Figure 15] 1 is a graph showing the HPLC chart of the physically modified starch of Prototype Example 6. [Figure 16] 1 is a graph showing the HPLC chart of the physically modified starch of Prototype Example 7. [Figure 17] 1 is a graph showing an HPLC chart of the dextrin of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] In one embodiment of the present invention, a method for producing physically processed starch involves gelatinizing raw starch and subjecting it to multiple stages of physical processing to reduce the viscosity, thereby lowering the viscosity to a level that allows spray drying without reducing the concentration, and producing starch that is soluble in water. The raw starch is composed of amylose, amylopectin, etc. In this amylose, α-D-glucopyranose is linked in a linear chain via α-1,4 bonds, and in amylopectin, α-D-glucopyranose has linear portions formed by α-1,4 bonds and branched portions formed by α-1,6 bonds.

[0022] The raw starch is not particularly limited, and any type that is commercially available and easily available can be used. For example, starches from corn (cornstarch), wheat, barley, rye, rice, sweet potato (cane sugar), potato (potato starch), pea, edamame, tapioca, etc., as well as starches from glutinous species such as glutinous wheat, glutinous millet, and glutinous barnyard millet, waxy cornstarch, glutinous rice starch, etc. can be used.

[0023] Since the viscosity, water solubility, and other properties of physically modified starch can be adjusted by changing the raw materials, a mixture of these raw materials may be used. Amylopectin has properties such as easy gelatinization, resistance to retrogradation, and transparency of aqueous solution. For this reason, waxy corn starch, which is composed of almost 100% amylopectin, can be stably used as a raw starch and is suitable for the manufacturing method of the present invention.

[0024] As shown in the schematic diagram of one embodiment of FIG. 1, the manufacturing method of the present invention involves gelatinizing a mixed slurry of starch raw material and water, and performing physical treatment in multiple steps to obtain physically processed starch with appropriate viscosity and solubility in water. The multiple physical treatments are performed continuously without going back through the steps, which improves manufacturing efficiency. First, the starch raw material is mixed with water to obtain a slurry (starch mixing step S1). The concentration of the starch raw material is 25% by weight or less. If the concentration of the starch raw material is higher than 25% by weight, the viscosity of the gelatinized starch obtained in the gelatinization step becomes too high, which may result in longer processing times in the subsequent steps or excessive load on the machine, which is considered to result in a decrease in efficiency. In addition, if the concentration is too low, the drying efficiency decreases and the yield decreases, so it is preferable to set the concentration to 5% by weight or more.

[0025] After the starch mixing step, the pH of the slurry may decrease due to contact with microorganisms or air, so the pH of the slurry is adjusted as necessary. Caustic soda, hydrochloric acid, etc. are added, and appropriate treatment is performed depending on the application of the physically processed starch (pH adjustment step S2). If the pH adjustment of the slurry is not required, the pH adjustment step can naturally be omitted.

[0026] The slurry is then pressurized and heated to gelatinize (gelatinize) it to produce gelatinized starch (solution) (gelatinization step S3). The gelatinization of the raw starch (slurry) is carried out by a known method. For example, the slurry can be gelatinized at high temperature by applying steam to it and pressurizing it. In one embodiment of the present invention, the raw starch is gelatinized by applying steam and pressurizing it to 0.21 MPa for about 12 minutes. At this time, the liquid temperature of the solution rises to about 125°C.

[0027] Although omitted in the schematic diagram of the manufacturing method of the present invention shown in the figure, it is preferable to release the increased pressure as necessary to lower the temperature of the solution. For example, by creating a vacuum using a flash tank, the boiling point is lowered and the liquid temperature is lowered. By returning to normal pressure, the burden on the machine can be suppressed. This is significant from the viewpoint of equipment protection. The liquid temperature of the solution is preferably about 80 to 85°C. If the liquid temperature is too low, the viscosity of the solution becomes high, and there is a risk of increasing the equipment load in the first viscosity reduction step in the next step. In one embodiment of the present invention in which waxy corn starch is used as the raw starch, the 80°C viscosity of the solution at Bx10 at this time was approximately 257 mPa·s. The viscosity is not particularly limited, but it is preferable to set it to about 250 to 4500 mPa·s from the viewpoint of equipment protection, including the case where potato starch or tapioca starch with high viscosity is used.

[0028] The viscosity at Bx10 was measured by diluting the gelatinized starch obtained in each step to Bx10 and measuring the viscosity at a liquid temperature of 80°C using a "VISCO" (manufactured by Atago Co., Ltd.). The spindle was A1, the beaker size was L, and the measurement speed was set according to the viscosity.

[0029] Next, the gelatinized starch is subjected to a first physical treatment to reduce the viscosity by 15% or more from the viscosity in the previous step (first viscosity reduction step (S4)). In order to reduce the viscosity of the gelatinized starch, an operation is carried out in which the starch molecules are cut and decomposed to reduce the molecular weight. Although the starch molecules can be cut and decomposed by enzymes or the like, in the present invention, from the viewpoint of high efficiency, it is desirable that the first physical treatment is a shearing treatment using a rotational force. For example, a mixer, an emulsifier, or the like can be used for the shearing treatment.

[0030] The first physical treatment is performed for 3000 min at a solution temperature of 70°C or higher. -1 When the shearing treatment is performed with a rotational force of 1000 to 2000 mm / s, the viscosity of the gelatinized starch (solution) can be efficiently reduced. The liquid temperature of the solution is preferably 80°C or higher from the viewpoint of reducing the load on the equipment. In addition, the higher the rotational force in the shearing treatment, the shorter the time required for the first physical treatment can be, so that the rotational force is preferably 3500 min -1 Furthermore, if in the first viscosity-reducing step the viscosity of the gelatinized starch is reduced by 25% or more from the viscosity in the previous step, the viscosity reduction in the subsequent steps will be more efficient.

[0031] The 80°C viscosity at Bx10 of the solution after the first viscosity reduction step is preferably adjusted to approximately 180 to 1200 mPa s. Although the 80°C viscosity at Bx10 of the solution after the first viscosity reduction step depends on the 80°C viscosity at Bx10 of the solution after the gelatinization step, adjusting it to the above range as a guideline improves the efficiency of the next step and subsequent viscosity reductions and is significant from the standpoint of equipment protection.

[0032] After the first viscosity reduction step is completed, a second physical treatment is carried out to further reduce the viscosity of the solution by 80% or more, which was reduced in the first viscosity reduction step (second viscosity reduction step S5). Since this step significantly reduces the viscosity of the solution, it is preferable to shear the solution under high pressure conditions to break and decompose the starch molecules. For example, the efficiency can be increased by continuously treating the solution with a high-pressure homogenizer.

[0033] In the second physical treatment, when the liquid temperature is 70°C or higher and pressurized to 30 to 60 MPa, the viscosity of the gelatinized starch (solution) can be efficiently reduced. From the viewpoint of reducing the load on the equipment, it is more preferable that the liquid temperature of the solution is 80°C or higher. In addition, a lower pressure reduces the load on the equipment, which is preferable from the viewpoint of reducing the load on the equipment.

[0034] The 80°C viscosity at Bx10 of the solution after the second viscosity-reduction step is preferably adjusted to approximately 25 to 85 mPa s. Although the 80°C viscosity at Bx10 of the solution after the second viscosity-reduction step depends on the 80°C viscosity at Bx10 of the solution after the first viscosity-reduction step, by adjusting it to the above range as a guideline, it is believed that the efficiency of the next and subsequent viscosity-reduction steps will be improved and the solubility will be improved.

[0035] After the second viscosity-reducing step is completed, a third physical treatment may be carried out to further reduce the viscosity of the solution reduced in the second viscosity-reducing step by 2% or more (third viscosity-reducing step S6). This step allows for fine adjustment of the viscosity of the solution, thereby making it possible to appropriately adjust the solubility or viscosity of the resulting low-viscosity starch, and thus to obtain physically processed starch with the desired physical properties. Since the starch has already been subjected to a certain degree of viscosity-reducing step, it is more efficient to subject the starch to shear treatment under high-pressure conditions to break and decompose the starch molecules. For example, it is preferable to carry out continuous treatment using a high-pressure homogenizer.

[0036] In the third viscosity reduction step, when the liquid temperature is 70°C or higher and pressurized to 5 to 35 MPa and sheared, the viscosity of the gelatinized starch (solution) can be efficiently reduced. From the viewpoint of reducing the load on the equipment, it is more preferable that the liquid temperature of the solution is 80°C or higher. In addition, a lower pressure reduces the load on the equipment, which is preferable from the viewpoint of reducing the load on the equipment.

[0037] The 80°C viscosity at Bx10 of the solution after the third viscosity-reduction step is preferably adjusted to approximately 15 to 70 mPa s. Although the 80°C viscosity at Bx10 of the solution after the third viscosity-reduction step depends on the 80°C viscosity at Bx10 of the solution after the second viscosity-reduction step, it is believed that the desired solubility and viscosity can be obtained by adjusting the viscosity within the above range as a guideline.

[0038] The reduced-viscosity starch obtained through the first, second and third viscosity-reducing steps is dried to form a granular (powdered) material (drying step S7). The drying method in the drying step is not particularly limited, and known drying methods such as spray drying, vacuum freeze drying and drum dryer are appropriately used. In particular, drying by the spray drying method can produce a highly efficient, high-quality and uniform physically processed starch. Although physically processed starch is a granular (powdered) material, the drying step may be omitted and the liquid reduced-viscosity starch may be used as is depending on the application.

[0039] The viscosity of the low-viscosity starch obtained through the first, second, and third viscosity-reduction steps is reduced to a level that allows spray drying without reducing the starch concentration, making it possible to produce physically processed starch with high efficiency. Since spray drying allows extrusion spraying at an extrusion pressure of approximately 5 to 20 MPa, efficient drying is possible while reducing the load on the equipment. There are no particular limitations on the hot air temperature as long as it allows drying of the low-viscosity starch.

[0040] The physically processed starch obtained by the manufacturing method of the present invention is preferably adjusted so that the minimum peak viscosity of the paste is 40% or more relative to the maximum peak viscosity of the paste, and the final viscosity is 60% or more. This index indicates that the difference in viscosity of the paste is small depending on the temperature range, and indicates that the properties of the physically processed starch added to foods and the like are unlikely to change depending on the temperature. Therefore, by adjusting the viscosity of the paste to the above range, the change in properties during heating and cooling can be reduced, making it easy to handle and allowing it to be used stably in various applications. For example, when the physically processed starch is added to bread, shrinkage of the bread when it cools down can be suppressed, and changes in properties and shape due to temperature changes can be made less likely to occur.

[0041] Regarding the viscosity of the paste, (1) physically modified starch is prepared into a 10% by weight aqueous suspension. (2) The aqueous suspension is stirred at 160 rpm using a Rapid Visco Analyzer and held at 50°C for 1 minute. (3) The temperature is then raised from 50°C to 95°C in 3 minutes 42 seconds, and held at 95°C for 5 minutes. (4) The temperature is then lowered from 95°C to 50°C in 3 minutes 48 seconds, and held at 50°C for 5 minutes. (5) The maximum peak viscosity, minimum peak viscosity, and final viscosity during the steps (2) to (4) are measured.

[0042] Furthermore, the molecular weight dispersity (weight average molecular weight / number average molecular weight) of the physically processed starch obtained by the production method of the present invention is preferably 13000 to 35000. Since the starch molecules are cut and decomposed in multiple stages, the molecular range of the starch molecules becomes broad, and the physically processed starch can have appropriate viscosity and solubility in water.

[0043] The weight average molecular weight (Mw) is one of the indicators of the average molecular weight used to understand the properties of natural polymer compounds such as starch, and is defined by the following formula (i). i is the molecular weight of the molecule present in the polymer, N i is the molecular weight M i is the number of molecules in

[0044]

number

[0045] As can be seen from formula (i), the weight average molecular weight (Mw) is sensitively affected by the size of the constituent molecules. Therefore, the effect of a very small amount of large molecules can be taken into consideration when determining the average molecular weight. In the physically processed starch of the present invention, the weight average molecular weight (Mw) is set to approximately 300 million to 800 million. If the weight average molecular weight (Mw) is small, the viscosity is insufficient and the desired viscosity cannot be obtained. If the weight average molecular weight (Mw) is large, the viscosity becomes high and handling becomes difficult. The weight average molecular weight is measured by a known high performance liquid chromatography method.

[0046] The number average molecular weight (Mn) is an index representing the average molecular weight per molecule, and is defined by the following formula (ii). i and N i is the same as that in the above formula (i). In the physically processed starch of the present invention, the number average molecular weight (Mn) is preferably about 10,000 to 40,000. If the number average molecular weight (Mn) is too small, the viscosity is insufficient and the desired viscosity cannot be obtained. If the number average molecular weight (Mn) is too large, the viscosity becomes high and handling becomes difficult. The number average molecular weight can be measured by a known high performance liquid chromatography method.

[0047]

number

[0048] As described above, the physically modified starch obtained by the present invention has water solubility and appropriate viscosity. For this reason, it can be suitably used as a food binder. Furthermore, the physically modified starch having such properties can be easily and reliably produced, and is useful as an alternative to conventional physically modified starches. EXAMPLES

[0049] [Preparation of physically modified starch] The physically processed starches of Prototype Examples 1 to 7 were produced under the following conditions. The raw materials and the conditions of the first to third physical treatments of each prototype are shown in Table 1 below, and the viscosity and viscosity reduction rate at Bx10 after the first to third viscosity reduction steps are shown in Table 2.

[0050] <Prototype example 1> An appropriate amount of water was added to commercially available waxy cornstarch ("Waxy Cornstarch IPY", manufactured by Nihon Shokuhin Kako Co., Ltd.) to obtain a 17% by weight slurry (starch mixing step). Hydrochloric acid and caustic soda were appropriately added to the slurry to adjust the pH to 6-7 (pH adjustment step). The pH-adjusted slurry was exposed to steam, pressurized, and gelatinized at a high temperature of 125°C to obtain gelatinized starch (gelatinization step). The gelatinized starch was then introduced into a flash tank and cooled to 85°C. At this time, the 80°C viscosity of the gelatinized starch at Bx10 was 257.3 mPa s. The gelatinized starch was then mixed in an emulsifier ("EB-0815 Type Emulder", manufactured by Izumi Food Machinery Co., Ltd.) for 3600 min. -1 The starch was sheared at 45 MPa to a viscosity of 214.3 mPa·s at 80°C in Bx10, a viscosity reduction of approximately 17% from the previous step (first viscosity reduction step). The starch was then sheared at 45 MPa pressure in a high-pressure homogenizer ("HV-1H4.5-18.5S homogenizer", manufactured by Izumi Food Machinery Co., Ltd.) to a viscosity of 36.8 mPa·s at 80°C in Bx10, a viscosity reduction of approximately 83% from the previous step (second viscosity reduction step). The starch was then continuously sheared at a pressure of 10 MPa in a second high-pressure homogenizer ("HV-1H4.5-18.5S homogenizer", manufactured by Izumi Food Machinery Co., Ltd.) to a viscosity of 35.9 mPa·s at 80°C in Bx10, a viscosity reduction of approximately 2% from the previous step, to obtain a low-viscosity starch (third viscosity reduction step). The thus obtained low-viscosity starch was spray-dried using a spray dryer ("CL-8 type spray dryer", manufactured by Okawara Kakoki Co., Ltd.) to obtain physically modified starch of Prototype Example 1.

[0051] <Prototype Example 2> Prototype 2 was produced under the same conditions as Prototype 1, except that the pressure conditions for the shear treatment in the second viscosity-reduction step were 48 MPa. The 80°C viscosity of the gelatinized starch at Bx10 was 293.3 mPa·s. The 80°C viscosity of the solution after the first viscosity-reduction step at Bx10 was 197.7 mPa·s, a viscosity reduction of approximately 33% from the previous step. The 80°C viscosity of the solution after the second viscosity-reduction step at Bx10 was 35.1 mPa·s, a viscosity reduction of approximately 82% from the previous step. The 80°C viscosity of the solution after the third viscosity-reduction step at Bx10 was 34.1 mPa·s, a viscosity reduction of approximately 3% from the previous step.

[0052] <Prototype 3> Prototype 3 was produced under the same conditions as Prototype 1, except that the pressure conditions for the shear treatment in the second viscosity-reduction step were 58 MPa and the pressure conditions for the shear treatment in the third viscosity-reduction step were 13 MPa. The 80°C viscosity of the gelatinized starch at Bx10 was 328.7 mPa·s. The 80°C viscosity of the solution after the first viscosity-reduction step at Bx10 was 214.3 mPa·s, a viscosity reduction of about 35% from the previous step. The 80°C viscosity of the solution after the second viscosity-reduction step at Bx10 was 26.8 mPa·s, a viscosity reduction of about 88% from the previous step. The 80°C viscosity of the solution after the third viscosity-reduction step at Bx10 was 21.0 mPa·s, a viscosity reduction of about 22% from the previous step.

[0053] <Prototype 4> Prototype 4 was produced under the same conditions as Prototype 1, except that the pressure conditions for the shear treatment in the second viscosity-reduction step were 40 MPa and the pressure conditions for the shear treatment in the third viscosity-reduction step were 22 MPa. The 80°C viscosity of the gelatinized starch at Bx10 was 358.6 mPa·s. The 80°C viscosity of the solution after the first viscosity-reduction step at Bx10 was 239.6 mPa·s, a viscosity reduction of about 33% from the previous step. The 80°C viscosity of the solution after the second viscosity-reduction step at Bx10 was 37.0 mPa·s, a viscosity reduction of about 85% from the previous step. The 80°C viscosity of the solution after the third viscosity-reduction step at Bx10 was 24.3 mPa·s, a viscosity reduction of about 34% from the previous step.

[0054] <Prototype 5> In prototype 5, the rotational force of the shear treatment in the first viscosity reduction process is 3000 min -1 The viscosity of the gelatinized starch was 310.8 mPa·s at 80°C in Bx10. The viscosity of the solution after the first viscosity-reduction step was 231.9 mPa·s at 80°C in Bx10, a viscosity reduction of approximately 25% from the previous step. The viscosity of the solution after the second viscosity-reduction step was 46.5 mPa·s at 80°C in Bx10, a viscosity reduction of approximately 80% from the previous step. The viscosity of the solution after the third viscosity-reduction step was 29.9 mPa·s at 80°C in Bx10, a viscosity reduction of approximately 36% from the previous step.

[0055] <Prototype 6> An appropriate amount of water was added to commercially available potato starch ("Superior Potato Starch", manufactured by KMC Amba) to obtain a 12% by weight slurry (starch mixing process). Hydrochloric acid and caustic soda were appropriately added to this to adjust the pH to 6-7 (pH adjustment process). Steam was applied to the pH-adjusted slurry, which was then pressurized and gelatinized at a high temperature of 125°C to obtain gelatinized starch (gelatinization process). The gelatinized starch was then introduced into a flash tank and cooled to 85°C. At this time, the 80°C viscosity of the gelatinized starch at Bx10 was 4348 mPa s. The gelatinized starch was then mixed in a disperser ("Homo Disper 2.5", manufactured by Primix Corporation) for 3600 min. -1The starch was sheared at 400°C to a viscosity of 1127mPa·s at Bx10, a viscosity reduction of approximately 74% from the previous step (first viscosity reduction step). The starch was then sheared at a pressure of 58MPa using a high-pressure homogenizer ("HV-0H07-3.7S homogenizer", manufactured by Izumi Food Machinery Co., Ltd.) to a viscosity of 77.6mPa·s at 80°C at Bx10, a viscosity reduction of approximately 93% from the previous step (second viscosity reduction step). The starch was then continuously sheared at a pressure of 35MPa using a second high-pressure homogenizer ("HV-0H07-3.7S homogenizer", manufactured by Izumi Food Machinery Co., Ltd.) to a viscosity of 64.4mPa·s at 80°C at Bx10, a viscosity reduction of approximately 17% from the previous step, to obtain a low-viscosity starch (third viscosity reduction step). The thus obtained low-viscosity starch was spray-dried using a spray dryer ("CL-8 type spray dryer", manufactured by Okawara Kakoki Co., Ltd.) to obtain physically modified starch of Prototype Example 6.

[0056] <Prototype 7> Prototype Example 7 was produced under the same conditions as Prototype Example 6, except that the raw material was tapioca starch ("Tapioca Starch", manufactured by Gaban Co., Ltd.) and the pressure conditions for the shear treatment in the second viscosity-reducing step were 56 MPa and the pressure conditions for the shear treatment in the third viscosity-reducing step were 24 MPa. The 80°C viscosity of the gelatinized starch at Bx10 was 4260 mPa·s. The 80°C viscosity of the solution after the first viscosity-reducing step at Bx10 was 645.1 mPa·s, a viscosity reduction of approximately 85% from the previous step. The 80°C viscosity of the solution after the second viscosity-reducing step at Bx10 was 48.0 mPa·s, a viscosity reduction of approximately 93% from the previous step. The 80°C viscosity of the solution after the third viscosity-reducing step at Bx10 was 40.6 mPa·s, a viscosity reduction of approximately 16% from the previous step.

[0057] [Table 1]

[0058] [Table 2]

[0059] [Viscosity measurement] The samples of Prototype Examples 1 to 7 are added with water to make a 10% by weight aqueous suspension of 30 g. The aqueous suspension is well dispersed and set in a Rapid Viscoanalyzer ("RVA4500", manufactured by Perten Instruments). The aqueous suspension is held at 50°C for 1 minute while stirring at a rotation speed of 160 rpm, and is heated from 50°C to 95°C in 3 minutes and 42 seconds by applying a continuous heating state, and is held at 95°C for 5 minutes. Then, the temperature is lowered from 95°C to 50°C in 3 minutes and 48 seconds by applying a continuous cooling state, and is held at 50°C for 5 minutes. The peak viscosity during this operation was measured to measure the maximum peak viscosity, minimum peak viscosity, and final viscosity. The maximum peak viscosity, minimum peak viscosity, final viscosity, minimum peak viscosity (%) relative to the maximum peak viscosity, and final viscosity (%) relative to the maximum peak viscosity of Prototype Examples 1 to 7 are shown in Table 3.

[0060] [Table 3]

[0061] The viscosity changes with temperature for Prototype Examples 1 to 7 are shown in graphs in Figures 2 to 8. The raw starch (waxy corn starch) used in Prototype Example 1 is used as Comparative Example 1, and the viscosity fluctuations with temperature for Comparative Example 1 are shown in graph form in Figure 9.

[0062] [Measurement of weight average molecular weight, number average molecular weight, and molecular weight dispersity] The weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight dispersity (Mw / Mn) were measured based on an HPLC (high performance liquid chromatography) system using a gel permeation chromatography column. The HPLC system used a differential refractometer "RID-20A" (Shimadzu Corporation), a pump "LC-20AD" (Shimadzu Corporation), a column oven "CTO-20A" (Shimadzu Corporation), and a column "SB-806HQ (inner diameter 8 mm x length 300 mm)" (Resonac Corporation).

[0063] The physically modified starches of Examples 1 to 7 were dissolved in pure water at a concentration of 1% by weight (solid content concentration), filtered using a 0.45 μm membrane filter, and then loaded into the above-mentioned HPLC system. The carrier for separating the components in the solution was pure water, the flow rate was 1.0 mL / min, and the column temperature was 70°C. In addition, SHODEX STANDARD P-82 (pullulan; peak top molecular weights 739000, 334000, 216000, 107000, 49700, 22000, 9800, and 6300) manufactured by Resonac Co., Ltd. was used as a standard substance with a known molecular weight. The molecular weight distribution data obtained by the HPLC system was analyzed using chromatogram analysis software "SICμ7Plus Data Station" manufactured by System Instruments Co., Ltd., and the weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight dispersity (Mw / Mn) were calculated. The Z-average molecular weight (M z ) is also used as an index for understanding the properties of natural polymer compounds such as starch and resin polymer compounds, and is calculated using the above-mentioned HPLC system and chromatogram analysis software. The weight-average molecular weight (Mw), number-average molecular weight (Mn), and molecular weight dispersity (Mw / Mn) of the dextrins ("Pinex (registered trademark) #2", manufactured by Matsutani Chemical Industry Co., Ltd.) of Prototype Examples 1 to 7 and Comparative Example 2 are shown in Table 4.

[0064] [Table 4]

[0065] 10 to 16 show the HPLC charts of Prototype Examples 1 to 7. FIG. 17 shows the HPLC chart of Comparative Example 2.

[0066] [Results and Discussion 1] As shown in Table 3 and Figures 2 to 8, in the prototypes 1 to 5 using waxy cornstarch as the raw material, the minimum peak viscosity was about 50% or more of the maximum peak viscosity, and the final viscosity was about 70% or more of the maximum peak viscosity. In addition, the prototypes 6 and 7 using potato starch or tapioca starch as the raw material also showed the minimum peak viscosity and the final viscosity relative to the maximum peak viscosity equivalent to the prototypes 1 to 5 using waxy cornstarch as the raw material.

[0067] In contrast, as shown in Table 3 and Fig. 9, Comparative Example 1 exhibited a tendency that the viscosity rose sharply once with heating and then decreased. The minimum peak viscosity of Comparative Example 1 was 30% of the maximum peak viscosity, and the final viscosity was 38%.

[0068] From the above, the physically processed starches of Prototype Examples 1 to 7 show little difference in viscosity depending on the temperature range, which means that the change in viscosity is small, demonstrating high stability when added to foods. In particular, Prototype Examples 1 to 5, which use waxy cornstarch as a raw material, were able to adjust the maximum peak viscosity to 71 to 86 mPa s by changing the production method, and therefore the viscosities of Prototype Examples 1 to 5 can be set arbitrarily to a level that is neither too high nor too low, making them highly practical physically processed starches.

[0069] In addition, in Prototype 6, in which the raw material was changed to potato starch, the viscosity of the gelatinized starch after gelatinization was very high, but by going through the first to third viscosity reduction steps, it was possible to easily produce a physically processed starch with a low viscosity, and the viscosity difference due to temperature range was suppressed. In Prototype 7, in which tapioca starch was used as the raw material, the viscosity difference due to temperature range was slightly larger than in Prototypes 1 to 5, which used waxy corn starch as the raw material, and Prototype 6, which used potato starch as the raw material, but was greatly improved compared to the comparative examples. Therefore, the production method of the present invention can be used without limiting the raw material.

[0070] Next, as shown in Table 4 and Figures 10 to 17, it is understood that Prototype Examples 1 to 7 have a high molecular weight dispersity and a wide molecular weight distribution, and have both molecules in the high molecular weight region that cause viscosity and molecules in the low molecular weight region that cause solubility in water. In other words, since Prototype Examples 1 to 7 have molecules in a wide molecular weight region, they have composite properties that combine properties in accordance with each molecular region. In contrast, the distribution of Comparative Example 2 has sharp molecules in the low molecular weight region, and therefore it is understood that although it has solubility in water due to molecules in the low molecular weight region, its viscosity is insufficient.

[0071] Next, in addition to Prototype Examples 1 to 7 and Comparative Example 2, the following samples were subjected to a dissolution evaluation to evaluate the state when dissolved in water and an adhesion evaluation to evaluate the adhesion to food. Furthermore, the effects on taste, texture, and odor when added to food were evaluated.

[0072] <Comparative Example 3> In Comparative Example 3, gelatin ("Zellice (registered trademark)", manufactured by Zellice Co., Ltd.) was used.

[0073] <Comparative Example 4> In Comparative Example 4, modified starch (starch octenyl succinate) ("Nyuka W", manufactured by Nippon Starch Chemical Co., Ltd.) was used.

[0074] <Comparative Example 5> In Comparative Example 5, pullulan (manufactured by Hayashibara Co., Ltd.) was used.

[0075] [Dissolution evaluation] Prototype Examples 1 to 7 and Comparative Examples 2 to 5 were dissolved in water of different temperatures, and the solubility of the prototypes and each comparative example was evaluated. The prototypes and each comparative example were dissolved in room temperature water (liquid temperature 20°C) or warm water (liquid temperature 80°C) and adjusted to a viscosity (approximately 28 mPa·s) that could be sprayed with a spray bottle. Solubility was scored as "3 points" for those that were soluble in cold water, and "1 point" for those that were soluble only in warm water. For handleability, solutions that were easy to prepare and easy to handle in the process were scored as "3 points," and those that were not scored as "1 point." The odor of the solution was checked, and those that had no odor or only a slight odor were scored as "3 points," and those that had an odor were scored as "1 point." These evaluation points were added together to give an overall evaluation. The viscosity of the solution was measured using a viscometer ("VISCO," manufactured by Atago Co., Ltd.) with a spindle of A1, a beaker size of S, and a measurement speed of 250 rpm. The results are shown in Tables 5 and 6.

[0076] [Table 5]

[0077] [Table 6]

[0078] [Binding evaluation] One pump of each of the solutions of prototypes 1 to 7 and comparative examples 1 to 5 prepared in the above-mentioned dissolution evaluation was sprayed onto a biscuit ("Harvest (registered trademark)" manufactured by Tohato Co., Ltd.), and then white sesame seeds were sprinkled on top and added, followed by heating and drying at 85°C for 5 minutes. The amount of white sesame seeds that had fallen off was then measured by turning the biscuit upside down. Those with a falling amount of 0 to less than 3% were given "10 points," those with a falling amount of 3 to less than 5% were given "7 points," those with a falling amount of 5 to less than 10% were given "3 points," and those with a falling amount of 10% or more were given "1 point." The results are shown in Tables 7 and 8.

[0079] [Table 7]

[0080] [Table 8]

[0081] Finally, the biscuits made in the above-mentioned adhesion evaluation were eaten and their effects on taste, texture, and smell were evaluated. Those that did not affect the taste of the biscuits were given a score of "3 points," and those that did affect it were given a score of "1 point." Those that did not affect the texture when the biscuits were chewed were given a score of "3 points," and those that did affect it were given a score of "1 point." Those that did not affect the smell of the biscuits were given a score of "3 points," and those that did affect it were given a score of "1 point." These scores were added up to give an overall score.

[0082] [Table 9]

[0083] [Table 10]

[0084] In addition, the dextrin of Comparative Example 2 did not affect the taste or smell, but the crispy texture of the biscuits was lost. The gelatin of Comparative Example 3 did not affect the texture, but had an odor and affected the taste. The modified starch of Comparative Example 4 had an odor and affected the taste, and the crispy texture of the biscuits was lost. The pullulan of Comparative Example 5 did not affect the taste or smell, but the crispy texture of the biscuits was lost.

[0085] [Results and Discussion 2] As described in the above Result and Discussion 1, according to the production method of the present invention, by carrying out physical processing in multiple stages, it is possible to easily and reliably produce physically processed starch while reducing the load on the equipment, and the obtained physically processed starch has molecules with a wide molecular range. From this, it was understood that it is possible to obtain physically processed starch with complex properties, including moderate viscosity and solubility in water.

[0086] The physically processed starch obtained had the above-mentioned physical properties, good solubility in water, good binding properties, no odor that would affect food, and no effect on the taste or texture.

[0087] From the above, the present invention makes it possible to obtain physically processed starch highly efficiently using a simple process, and the obtained physically processed starch has solubility in water and appropriate viscosity, and does not have any adverse effects when added to food, so it can be said to be an easy-to-handle physically processed starch. [Industrial Applicability]

[0088] The method for producing physically modified starch of the present invention is capable of producing a starch solution with low viscosity without reducing the concentration through a simple and continuous process, and therefore improves the drying efficiency and enables the production of physically modified starch simply and efficiently. Furthermore, the physically modified starch obtained has a suitable viscosity and good solubility in water, making it easy to handle and promising as a new alternative food to conventional food additives such as thickeners.

Claims

1. A processed starch having a minimum peak viscosity of 40% or more relative to the maximum peak viscosity of the paste measured by the following measurement method, and a final viscosity of 60% or more. <Measurement method> (1) Prepare a 10% by weight suspension of the modified starch in water. (2) The aqueous suspension is stirred at 160 rpm using a Rapid Visco Analyzer and maintained at 50° C. for 1 minute. (3) Next, the temperature is increased from 50° C. to 95° C. in 3 minutes and 42 seconds, and then maintained at 95° C. for 5 minutes. (4) Next, the temperature is cooled from 95° C. to 50° C. in 3 minutes and 48 seconds, and then held at 50° C. for 5 minutes. (5) Measure the maximum peak viscosity, minimum peak viscosity, and final viscosity during the steps (2) to (4).

2. 2. The processed starch according to claim 1, wherein the molecular weight dispersity (weight average molecular weight / number average molecular weight) is 13,000 to 35,000.

3. 3. The modified starch according to claim 1 or 2, which is a food binder.

4. 3. The modified starch according to claim 1 or 2, wherein the starch raw material is waxy corn starch.

5. 4. The modified starch according to claim 3, wherein the starch raw material is waxy corn starch.

Citation Information

Patent Citations

  • Method for producing starch degradation product

    JP1998506425A

  • Method for producing liquid from gel and method for producing powder

    JP4288381B2